CHARACTERIZATION OF A PROGRAM OF LABOR GYMNASTIC AS PREVENTION AND REDUCTION OF RSI / WMSD (Fiep Bulletin - online, 2013)
Labor gymnastic is based on the valuation of the practice of specific activities as a means of further improving the quality of life of its employees, as well as promote integration, socialization and ultimately improve productivity. The aim of this study was to develop practical actions using gymnastics for prevention and reduction of repetitive strain injuries (RSI) / work-related musculoskeletal disorders (MSDs) and improving the quality of life of employees of the company. This study evaluated 120 individuals who were part of the sample group and the population equaled up to 130 individuals of both sexes, and these same represented as follows, n = 102 (85%) female subjects with mean age (27.8 ± 7.9) years, n = 18 (15%) male subjects with mean age (27 ± 9.8) years. In order to seek or obtain the data necessary to achieve the proposed goals made use of the following research instruments: questionnaire investigation called "Subjective Evaluation of Localized Pain" as (OLIVEIRA, 2002), the investigative questionnaire "Profile of Individual Lifestyle (Pentacle Welfare)" as (NAHAS, 2010). According to the data obtained in the Pentacle welfare, there was a difference between the results of pre-test and post-test, profile changes occurring negative to positive. We obtained data on the prevalence of pain, it may be noted that the proposed activities of gymnastics contributed to an improvement in the aforementioned regions (left shoulder, left wrist, cervical, dorsal region) occurs a major difference between the pre and post -test.
Keywords: Labor gymnastic; Prevention; RSI / WMSD